Clinical presentation and neurovascular manifestations of cardiac myxomas and papillary fibroelastomas: a retrospective single-institution cohort study - Mathavan, Akshay; Mathavan, Akash; Krekora, Urszula; Mathavan, Mohit; Rodriguez, Vanessa; Altshuler, Ellery; Nguyen, Brianna; Ruzieh, Mohammed (Frontiers in Cardiovascular Medicine, 2023)
Background: Primary cardiac tumors are often benign and commonly present as cardiac myxomas (CM) or papillary fibroelastomas (CPFE). There is a paucity of prognostic indicators for tumor burden or potential for embolic cerebrovascular events (CVE). This study was performed to address these gaps. Methods: Medical records at the University of Florida Health Shands Hospital between 1996 and 2021 were screened to identify patients with CM or CPFE. Clinical features, echocardiographic reports, and CVE outcomes were quantitatively assessed. Results: 55 patients were included in the study: 28 CM (50.9%) and 27 CPFE (49.1%). Baseline patient characteristics were similar between patients. Neutrophil-lymphocyte ratio was correlated (p< 0.005 in all cases) to three metrics of tumor size in both CM (r= 64-67%) and CPFE (r= 56-59%). CVE were the presenting symptom in 30 (54.5%) cases. CVE recurrence was high; the five-year CVE recurrence rate in patients with tumor resection was 24.0% compared to 60.0% without resection. No baseline patient characteristics or tumor features were associated with an initial presentation of CVE compared to any other indication. On univariate analysis, prolonged duration to surgical resection, left atrial enlargement, male sex, and a neutrophil-lymphocyte ratio> 3.0 at follow-up were significantly associated with five-year CVE recurrence. Left atrial enlargement and a neutrophil-lymphocyte ratio> 3.0 at follow-up remained significantly associated on multivariate analysis. Conclusion: Neutrophil-lymphocyte ratio may prognosticate tumor size and recurrence of neurologic events. An increased risk of CVE within five years of mass resection is almost exclusive to patients initially presenting with CVE.